(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2022)
The aim of this work was to investigate if men and women differed significantly in the distribution of endowments in a dictatorial game context, after the accomplishment of a cooperative task, when interacting directly one with another (Study 1), and when interaction is intermediated by the researcher (Study 2). The experimental task consisted of putting together a puzzle, and then distribute vouchers tickets in the model of a Dictatorial Game. One hundred twenty undergraduates (80 in Study 1 and 40 in Study 2) were organized into three types of pairs: men only, women only, or mixed. The distribution and expectation of receiving vouchers were not influenced by gender and, in general, participants tended to equality in all experimental conditions. Results suggest that participants appraise their partners’ work and try to compensate them, thus contributing to egalitarianism and pro-sociability, even in a context of a Dictator Game.